A "happiness test" for the new measures of national well-being: How much better than GDP are they? - Jan Delhey; Christian Kroll (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
Across the globe there is growing skepticism about the usefulness of GDP as a measure of national well-being. Consequently, several alternative quality-of-life (QOL) measures were developed which either aim at healing the GDP, complementing it, or replacing it. This chapter portrays some of these new measures and puts them to a happiness test: compared to the GDP, are the new QOL measures better able to capture what makes people happy and satisfied with their lives? Using data for 34 OECD societies, we can show that from a happiness perspective, there is-surprisingly-little wrong with the GDP, and most alternative QOL measures do not outperform GDP. Yet, one measure actually does a better job: the OECD's Better Life Index which is particularly effective when it comes to predicting subjective well-being in the richest OECD countries. In sum, the chapter demonstrates that a happiness perspective can add important insights along the way to facilitate the search for a new, widely accepted, internationally comparable measure of well-being.
Keywords: I31; 300; Better Life Index; GDP; happiness; Human Development Index; life satisfaction; national well-being; quality of life; Lebensqualität; Entwicklungsindikator; Zufriedenheit; Messung; Sozialprodukt; Kritik; OECD-Staaten